2021
DOI: 10.1051/e3sconf/202129901009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Bubble Acoustic Characteristics of Elliptical Nozzles

Abstract: Bubble acoustic signals were reported experimentally using five different nozzles with the same exit cross-sections. The bubble morphology was captured by a home-made experiment setup, which could synchronously obtain images of two perpendicular directions. Short-Time Fourier Transform and synchronization of video and audio were adopted to analyse the acoustic signal. Results demonstrated that the sound pressure of symmetrical bubble formation was higher than that of asymmetrical bubble formation, while the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Moreover, the phenomenon of almost uniform pressure distribution and non-uniform velocity distribution within the bubble is found, which is basically in accordance with the results of experimental studies on underwater explosive charge performed by Liang [15] and Poplavski [16]. The experimental research on the gas jet generated by underwater detonation employs mostly pressure measurements and high-speed photography combined with particle image velocimetry (PIV) techniques to obtain the pressure oscillation characteristics of the field and the typical phenomena of the bubble evolution, such as bubble expansion, shrinking, and necking [17][18][19].…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, the phenomenon of almost uniform pressure distribution and non-uniform velocity distribution within the bubble is found, which is basically in accordance with the results of experimental studies on underwater explosive charge performed by Liang [15] and Poplavski [16]. The experimental research on the gas jet generated by underwater detonation employs mostly pressure measurements and high-speed photography combined with particle image velocimetry (PIV) techniques to obtain the pressure oscillation characteristics of the field and the typical phenomena of the bubble evolution, such as bubble expansion, shrinking, and necking [17][18][19].…”
Section: Introductionsupporting
confidence: 82%
“…They found that the turbulence intensity at the air-liquid interface increased considerably with an increase in fluid density, resulting in poorer jet stability. Regarding the noise characteristics of underwater gas jets, the noise from low-speed jets is primarily caused by bubbles [18][19][20][21][22]. However, based on the research conducted by Liu et al [23], who used a large eddy simulation (LES) to analyze the flow structure and noise radiation of underwater supersonic jets, the noise generated by high-speed jets originated primarily from the shockwave structure of the jet.…”
Section: Introductionmentioning
confidence: 99%